Haiwan Jallalah dari Perspektif Islam: Analisis Fatwa Malaysia dan Negara Brunei Darussalam - Pauzi, Norhidayah; Man, Saadan (Jurnal Fiqh, 2015)
Feeding aquatic animal with non-halal food is frequently practised by a handful of breeders within and outside the country. Accordingly, the Malaysian National Fatwa Council Committee has issued a fatwa that the consumption of jallalah animals as haram or unlawful. However, the Mufti of Brunei Darussalam has come up with a different fatwa describing the consumption of jallalah animals as permissible and lawful in Islam. The difference of fatwas regarding halal or lawful status of the consumption jallalah animals has indeed created confusion to the Muslim community in Malaysia. This research focuses on the concept of jallalah animals from the Islamic perspective and analysis on the fatwas in Malaysia and Brunei Darussalam pertaining to the issue. The methodology used in this study is the method of documentation and observation. From the study,it is found that two main factors contribute to the differences in fatwas on jallalah animals between Malaysia and Brunei Darussalam, i.e. –the different standards of halal food: MS1500:2009 and PBD 24:2007; and different sources of literature references by both parties.